2015
DOI: 10.3389/fphys.2015.00325
|View full text |Cite
|
Sign up to set email alerts
|

Complex Coordination of Cell Plasticity by a PGC-1α-controlled Transcriptional Network in Skeletal Muscle

Abstract: Skeletal muscle cells exhibit an enormous plastic capacity in order to adapt to external stimuli. Even though our overall understanding of the molecular mechanisms that underlie phenotypic changes in skeletal muscle cells remains poor, several factors involved in the regulation and coordination of relevant transcriptional programs have been identified in recent years. For example, the peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α) is a central regulatory nexus in the adaptation of muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 59 publications
4
81
0
Order By: Relevance
“…5B). Collectively, these results suggest that PGC-1α regulates BNP gene expression in conjunction with AP-1 and ERRα, similarly to what has been described for vascular endothelial growth factor and other PGC-1α target genes8.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…5B). Collectively, these results suggest that PGC-1α regulates BNP gene expression in conjunction with AP-1 and ERRα, similarly to what has been described for vascular endothelial growth factor and other PGC-1α target genes8.…”
Section: Resultssupporting
confidence: 74%
“…PGC-1α induces genes involved in mitochondrial biogenesis, oxidative phosphorylation, vascularization and the contractile apparatus to enable a higher endurance capacity by co-activating an array of nuclear receptors and other transcription factors in a poorly understood complex transcriptional network89. In addition to the effects on energy metabolism in response to exercise, PGC-1α also has an immunomodulatory role1.…”
mentioning
confidence: 99%
“…This divergence is one of the very few parameters for which the PGC-1α-overexpressing and bona fide oxidative fibers are clearly different. In regard to most other metabolic and contractile properties, skeletal muscles of mTG animals closely mimic the phenotype of oxidative muscles [29]. Thus, the mechanistic underpinnings that control the diametrically opposite outcome between PGC-1α-overexpressing fibers with low vis-à-vis oxidative and endurance-trained muscle with high SC count is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the cyclin D1-CDK4 axis impacts specific aspects of metabolic regulation. Peroxisome-proliferator-activated receptor (PPAR)-γ coactivator-1α (PGC-1α) regulates mitochondrial biogenesis, and acts as a transcriptional regulator that controls the expression of antioxidant genes, energy fuel selection, muscle fiber differentiation and transformation [103]. A recent study revealed that cyclin D1-CDK4 can modulate PGC-1α acetylation, putatively through GCN5 phosphorylation; moreover, the cyclin D1 T286A mutant can constitutively acetylate PGC-1α [104].…”
Section: The Biological Functions Of Cyclin D1mentioning
confidence: 99%